2008
DOI: 10.1007/s10488-008-0196-5
|View full text |Cite
|
Sign up to set email alerts
|

Benefit Limits for Behavioral Health Care in Private Health Plans

Abstract: Data from a nationally representative sample of private health plans reveal that special lifetime limits on behavioral health care are rare (used by 16% of products). However, most plans have special annual limits on behavioral health utilization; for example, 90% limit outpatient mental health and 93% limit outpatient substance abuse treatment. As a result, enrollees in the average plan face substantial out-of-pocket costs for long-lasting treatment: a median of $2,710 for 50 mental health visits, or $2,400 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…2 VOLUME 4 • ISSUE 3 www.hospitalpediatrics.org There are multiple obstacles to accessing psychiatric treatment, especially inpatient psychiatric hospitalization. Insurance benefi ts for inpatient and outpatient mental health treatment have historically been capped, [3][4][5] limiting patients' access to care and providers' reimbursement for denied days of treatment. Available psychiatric beds have decreased substantially in the United States 6 while psychiatric hospitalization rates have increased.…”
Section: Impact Of Boarding Pediatric Psychiatric Patients On a Medicmentioning
confidence: 99%
“…2 VOLUME 4 • ISSUE 3 www.hospitalpediatrics.org There are multiple obstacles to accessing psychiatric treatment, especially inpatient psychiatric hospitalization. Insurance benefi ts for inpatient and outpatient mental health treatment have historically been capped, [3][4][5] limiting patients' access to care and providers' reimbursement for denied days of treatment. Available psychiatric beds have decreased substantially in the United States 6 while psychiatric hospitalization rates have increased.…”
Section: Impact Of Boarding Pediatric Psychiatric Patients On a Medicmentioning
confidence: 99%
“…Although the National Compensation Survey shows very high rates of employee coverage for SUDs treatment, studies by Gabel et al (2007) and Hodgkin, Horgan, Garnick, and Merrick (2009) document that within that coverage, significant coverage limits are imposed on use along with higher copayments. Hodgkin et al have estimated that participants in the average private plan face out of pocket costs of approximately $2,400 for 50 SA visits.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this mandate, however, consumers continued to experience differential limits on the number of visits and covered days, as well as greater out-of-pocket expenses for behavioral health services compared with medical care. 217 In response, the federal government passed the Mental Health Parity and Addiction Equity Act, which was implemented in 2010. 217 Several studies have demonstrated that the Mental Health Parity and Addiction Equity Act increased coverage for behavioral health services and use of such services.…”
Section: Parity For Insurance Coverage and Adequacy Of Mentalmentioning
confidence: 99%
“…217 In response, the federal government passed the Mental Health Parity and Addiction Equity Act, which was implemented in 2010. 217 Several studies have demonstrated that the Mental Health Parity and Addiction Equity Act increased coverage for behavioral health services and use of such services. It also reduced out-of-pocket expenses for consumers covered under both private and public health plans, [218][219][220] including the Federal Employee Health Benefits Program (FEHBP).…”
Section: Parity For Insurance Coverage and Adequacy Of Mentalmentioning
confidence: 99%